Exploring the Lived Experiences of Mothers of Children with Intellectual Disabilities in Rural Kenya - MANYARA, NANCY KARWITHA (Journal of Humanities and Social Sciences Studies, 2020)
Approximately 20% of children and youths globally experience some form of intellectual disability rendering them dependent on parents and other caregivers for the performance of daily tasks of living. Looking after these children is very challenging for the caregivers. This mixed methods study sought to define the lived experiences of mothers of children with intellectual disabilities in their daily care of the children. Standard questionnaires and structured interviews were used to collect data from 94 mothers of children with intellectual disabilities living in Ongata Rongai, Kajiado County, Kenya. The study found that mothers experience strain of care, financial difficulties, stigma and discrimination and, lack of adequate specialized education, health and rehabilitation care. Mothers cope with these challenges through spirituality, resilience, hope, love and acceptance and utilizing the available rehabilitation and educational facilities. The study recommends increased provision and access to education and rehabilitation for the children and, psychosocial support for the mothers raising children with intellectual disabilities to lessen the burden of care.